Mean platelet volume/platelet count ratio can predict the recurrence-free survival rate of patients after complete resection of gastrointestinal stromal tumors - Du, Xinlian; Zang, Xinxin; Zhang, Hanbo; Liu, Lijia; Xu, Ying; Li, Xuedong; Mou, Ruishu; Xu, Haitao; Zhu, Jiuxin; Xie, Rui (Frontiers in Oncology, 2024)
PurposeThe aim of this study is to compare mean platelet volume/platelet count ratio (PVPR) and other indicators’ predictive abilities. Simultaneously, a new nomogram for predicting recurrence-free survival (RFS) after gastrointestinal stromal tumors (GISTs) R0 resection was developed.MethodsFrom January 2010 to July 2019, 295 patients with GIST who were operated on at Harbin Medical University Cancer Hospital were retrospectively reviewed. With a 4-year RFS as the end point, using the Kaplan–Meier methods and log rank test, and then conducting Cox regression analysis, we compared and identified meaningful indicators for predicting prognosis. Finally, a nomogram was developed and validated using calibration curves.ResultsThe receiver operating characteristic curve indicated that a cutoff point of 0.044 was the ideal threshold for PVPR, and patients were divided into a high-PVPR group (≤0.044) and a low-PVPR group (>0.044). Kaplan–Meier curves suggested that PVPR>0.044 had obvious associations with better RFS (p < 0.001). In accordance with multivariate analysis, PVPR (>0.044 vs. ≤0.044) (p = 0.005), National Institutes of Health (NIH) risk category (p < 0.001), and Ki-67 (p = 0.005) were the independent prognostic indicators of RFS. Tumor size, gastrointestinal bleeding, mitotic index, NIH risk category, CD34, and Ki-67 all exhibited an obvious correlation with PVPR (all p < 0.05). The nomogram’s probability of concordance was 0.823, indicating that the nomogram predictions were well calibrated.ConclusionIn GISTs, RFS can be independently predicted by PVPR. Patients with higher PVPR have better RFS. The nomogram including PVPR could be used to assist clinical treatment decision-making.